# Mathematical Induction using a strong hypothesis

#### mamma_mia66

1. The problem statement, all variables and given/known data
If a0=1, and a1=2, and

an=(a(n-1))^2/an-2 for n>=2,
prove by induction that an=2^n for n>=0

2. Relevant equations

3. The attempt at a solution
(B) a0=1=2^0=1 yes is true
a1=2=2^1=2 yes is true

(I) ak=(2k-1)^2/2k-2=2k

Is it true that what I solved. It seems very easy.

I started first with a(k+1)=(a(k+1-1))^2/a(k+1-2)=
(2k)^2(k-1)=2(k+1)
Please someone help if I am doing something wrong. I will appreciate. Thank you.

Related Calculus and Beyond Homework News on Phys.org

#### Tedjn

It seems that you have the right idea, but I do not know what is different between (I) and your solution for ak+1. Where precisely is your inductive hypothesis?

#### Dick

Homework Helper
It IS very easy. So your induction step is: if a_{k-1}=2^(k-1) and a_{k-2}=2^(k-2) then a_k=2^(k) (by doing the algebra you doubtless did). It looks fine to me.

#### mamma_mia66

That is where I am confused. I know that I need to fallow the form an=2^n

Then I don't need to do a(k+1)....

I did so many problems in my HW and now I don't get it what I am doing Thank you guys.

### Physics Forums Values

We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling
We Value Civility
• Positive and compassionate attitudes
• Patience while debating
We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving